Health-related programs to prevent the developmental delay in children with stunting in Petung Village, Pakis, Magelang District - Sumarno Adi Subrata; Nurhidayah Nurhidayah; Halima Nur Aisya; Klara Sinta Oktaviani Budi Martani; Karisma Putri Aryani (Community Empowerment, 2022)
Stunting is still a serious problem in Magelang Regency, especially in Petung Village, Pakis, Magelang Regency. The recent data showed that 41 children having stunting. However, now there are 13 children. Although the number has decreased, some residents have complained about this. Therefore, the Integrated Community Service Program (PPMT) was initiated to reduce the case of stunting. The programs offered in this activity are the socialization of stunting material, play therapy and assistance in making additional food. This activity took place from December 13, 2021 to January 31, 2022. During this activity, the community was very enthusiastic about participating, they even actively asked questions, discussed with students and lecturers. This group hopes that the PPMT program can be a solution in alleviating stunting cases in Petung Village.